Static and incremental overlapping clustering algorithms for large collections processing in GPU - Soler, Lázaro Janier González; Suárez, Airel Pérez; Fernández, Leonardo Chang (Informatica, 2017)
There are several problems in Pattern Recognition and Data Mining that, by their inherent nature, consider that objects could belong to more than one class; that is, clusters can overlap each other. OClustR and DClustR are overlapping clustering algorithms that have shown, in the task of documents clustering, the better tradeoﬀ between quality of the clusters and eﬃciency, among the existing overlapping clustering algorithms. Despite the good achievements attained by both aforementioned algorithms, they are O(n2) so they could be less useful in applications dealing with a large number of documents. Moreover, although DClustR can eﬃciently process changes in an already clustered collection, the mount of memory it uses could make it not suitable for applications dealing with very large document collections. In this paper, two GPU-based parallel algorithms, named CUDA-OClus and CUDA-DClus, are proposed in order to enhance the eﬃciency of OClustR and DClustR, respectively, in problems dealing with a very large number of documents. The experimental evaluation conducted over several standard document collections showed the correctness of both CUDA-OClus and CUDA-DClus, and also their better performance in terms of eﬃciency and memory consumption.